Growth options and poverty reduction in Ethiopia: a spatial, economy-wide model analysis for 2004-2015 - Diao, Xinshen; Nin-Pratt, Alejandro; Gautam, Madhur; Keough, James; Chamberlin, Jordan; You, Liangzhi; Puetz, Detlev; Resnick, Danielle; Yu, Bingxin (International Food Policy Research Institute, 2005)
This study assesses which agricultural subsectors have the strongest capacity to drive economic growth and poverty reduction in Ethiopia, and what kind of agricultural and nonagricultural growth is needed to achieve the millennium development goal of halving the 1990 poverty rate by 2015. A spatially disaggregated, economywide model was developed under the study, enabling the analysis of growth and poverty reduction linkages at national and regional levels using national household surveys, agricultural sample surveys, geographic information systems, and other national and regional data. The study reveals that agriculture has the potential to play a central role in decreasing poverty and increasing growth in Ethiopia, primarily through growth in staple crops and livestock. Agricultural growth also requires concurrent investments in roads and other market conditions. At the subnational level, similar rates of agricultural growth have different effects on poverty, necessitating regionally based strategies for growth and poverty reduction.-- Authors' Abstract